On the complexity of IgE: The role of structural flexibility and glycosylation for binding its receptors - Plattner, Kevin; Bachmann, Martin F.; Vogel, Monique (Frontiers in Allergy, 2023)
It is widely known that IgE, the critical molecule of atopy, binds to the two Fc receptors (FcRs), FcRI and FcRII (CD23). While cross-linking of FcεRI bound IgE on effector cells such as basophils and mast cells triggers the allergic response, IgE binding to CD23 influences IgE serum levels and antigen presentation. In addition to binding to the FceRs, IgE can bind to other receptors, such as FcR, mainly in the form of a complex with the allergen. The uptake of the IgE-allergen complex could then contribute to the generation of anti-IgE IgG antibodies. As for IgG, the glycosylation of IgE plays a significant role in binding to receptors such as the low-affinity receptors galectin-3 and 9. Both receptors in their soluble forms bind IgE glycan-dependently and can take on regulatory tasks. In this review, we focus on IgE-binding receptors and discuss how glycosylation and complexation of IgE affect them.